A supervisão de estágio na formação profissional do assistente social: uma análise na Faculdade Paulista de Serviço Social de São Caetano do Sul - Nascimento, Juciléia Aparecida (2007)
This present study analyzed the process of the apprenticeship s supervision during the professional formation of social works in the College Paulista of Social Work at São Caetano do Sul (FAPSS/SCS), since the implantation of the current curriculum according to the curricular lines indicated by ABEPSS (Brazilian Association of Teaching and Research in Social Work) in the year of 1996. Our research, which has a quality character, involved a documental study of archives and materials of the proper College, such as the conceptions about supervision and apprenticeship; about them, we built a dossier trying to capture different ways to think the issue, in the scope of the thoughts of some authors who had treated this question in the Social Work. As our research s main subjects, we established them as the supervisors of FAPSS/SCS, and with them we had developed the focal group, instrument that allowed us to get more knowledge about the practice of supervision and the possible changes that happened in the apprenticeship s field after the new curriculum. We also had done interviews half structuralized with the representatives of the Department of Apprenticeship to learn about the supervision in the professional formation before and during the implantation of the current curriculum. The most substantive change pointed by the supervisors and which was observed in the FAPSS/SCS, it was the introduction of the monthly workshops, that, although those workshops were indicated as important, they are not enough to reach a bigger approach between the College and the apprenticeship s field, because of the limitations e contradictions in the daily dynamics of the institutions where happens the training period. Another aspect that it is not treated in the curriculum, even though it has been emphasized by the supervisors, it is the need of preparation in the moment of graduation to the exercise of the supervision. Still today, there are many issues that keep worrying the professionals in the moment of the apprenticeship s supervision, indicating the needs to also make it priority in the professional formation of social works, always having in mind the articulation between all the subjects involved in this process